Inflexibility and Corporate Credit Spreads - Xu, Zhaofeng; An, Zhe; Jong, Abe de; Xia, Ying (The Review of Corporate Finance Studies, 2025)
Abstract This paper studies the role of scale inflexibility in explaining corporate credit spreads. We find robust evidence that firms with higher inflexibility have higher credit spreads. To mitigate the endogeneity concern, we employ a regression discontinuity design that uses the exogenous variations in labor adjustment costs resulting from close-call union elections. Furthermore, contraction inflexibility is more prominent in influencing credit spreads than expansion inflexibility is. Additionally, inflexibility increases credit spreads due to increased cash flow volatility and financial distress risk. Our findings highlight the importance of a firm’s ability to adapt to productivity shocks in fulfilling its debt obligations. (JEL G12, G30, G32)